SHARIA LAW AND SHARIA VIRTUES IN SHAPING THE MORALS OF GENERATION Z: AN INTEGRATIVE-INTERCONNECTIVE APPROACH - Novita, Liana; M, Amril (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The purpose of this study is to develop an integrative-interconnective relationship between shariah law and sharia virtues. This will build a solid foundation of understanding and knowledge to guide the moral development of Gen Z, who grew up in an era of rapid technological advancement. The method used is a qualitative approach by utilizing library research and in-depth content analysis of primary texts and leading academic journals. The results of the study indicate that between sharia law, sharia virtues and the morality of Gen Z, all three are inseparable. However, it needs to be reiterated that the position of sharia law is the basis of sharia virtues and sharia virtues becomes an instrument for morality. In this case, the morality of Gen Z is like its inherent characteristics (critical thinking) but critical thinking in the style of sharia virtues (islamic thinking) based on sharia virtues. So here is the integrative-interconnective in the three relationships of sharia law, sharia virtues and the morality of Gen Z is truly. The implication of this research is that Gen Z is no longer rigid in its morals because it has been given teleological values (sharia virtues). To avoid deviating from these teleological values (sharia law), it remains grounded in theological values (sharia law). In fact, Gen Z is given the freedom to determine values in the 21st century and remains within theological values (sharia law).